New dimensions of food security in Romania from the European perspective - Corina Ene; Mirela Matei (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Article outlines the key coordinates of food security at global, regional and national level, highlighting and analyzing requirements, transformations, limits and opportunities facing our country at this level, in the context of EU integration.
Keywords: 330; food security; sustainable development; social responsibility